SOCIAL MEDIA AND GENERATION-Z PARTICIPATION IN ENVIRONMENTAL COMMUNICATION: THE USE OF INSTAGRAM @PANDAWAGROUP THROUGH THE HONEYCOMB FRAMEWORK - Kurniawan Prasetyo; Sofwan Syauri (Asian Journal of Applied Communication, 2025)
Anjani, S., & Irwansyah, I. (2020). Peranan Influencer Dalam Mengkomunikasikan Pesan di Media Sosial Instagram [The Role of Social Media Influencers in Communicating Messages Using Instagram]. Polyglot: Jurnal Ilmiah, 16(2), 203–229. https://doi.org/10.19166/pji.v16i2.1929 Chandrabuwono, A. B., & Atika, A. (2019). Komunikasi Lingkungan Masyarakat Sungai Tabuk dalam Menjaga Kebersihan Sungai. Metacommunication: Journal of Communication Studies, 4(2), 195–205. https://doi.org/10.20527/mc.v4i2.6939 Cornelio, G. S., Martorell, S., & Ardèvol, E. (2024). It is the Voice of the Environment that Speaks, Digital Activism as an Emergent Form of Environmental Communication. https://doi.org/10.1080/17524032.2023.2296850 Fadhlurrahman, M. A., Nisa, J., & Harjawati, T. (2025). The influence of Adiwiyata Program on students’ eco-friendly attitude. 1438, 012025. https://doi.org/10.1088/1755-1315/1438/1/012025 Goenawan, F. S. (2018). Sikap Masyarakat Surabaya Terhadap Iklan Indoeskrim Nusantara Versi Legenda Nusantara. Jurnal e-Komunikasi, 6(1), 1–11. Gui, Q., & Abdullah, A. R. (2024). Empirical Review of Attitude towards Eco-Friendly Hotels. https://doi.org/10.62051/ijgem.v3n1.13 Hastan, V. F., & Sukendro, G. G. (2022). Kreativitas Influencer dalam Mengampanyekan Self Love untuk Kesehatan Mental di Instagram. Prologia, 6(1), 25–32. https://doi.org/10.24912/pr.v6i1.10256 Iftakhar, I. (2022). Honeycomb Framework: Examining the Social and Personal Drivers of Fake News Sharing on Social Media Platforms. Journal of Development and Social Sciences, 3(III). https://doi.org/10.47205/jdss.2022(3-iii)01 Jafriyanti, S., & Lubis, E. E. (2021). Pengaruh Terpaan Akun Instagram @Zerowaste.Id_Official dalam Mengampanyekan Gaya Hidup Nol Sampah Terhadap Sikap Ramah Lingkungan Followers. Jurnal Online Mahasiswa FISIP, 8(1), 1–13. Kemp, S. (2023). Digital 2023: Indonesia. Dalam Datareportal.com. https://datareportal.com/reports/digital-2023-indonesia Khazim, D., Lase, D., & Sudirman. (2020). Optimasi Komunikasi Digital Bagi Freelancer & UUMKM Di Tengah Pandemi Covid-19. Jurnal Abdimas Mutiara, 1(2), 131–137. Kietzmann, J. H., Hermkens, K., McCarthy, I. P., & Silvestre, B. S. (2011). Social media? Get serious! Understanding the functional building blocks of social media. Business Horizons, 54(3), 241–251. https://doi.org/10.1016/j.bushor.2011.01.005 Kristanti, M., & Jokom, R. (2017). The Influence of Eco-friendly Attitudes on Tourists’ Intention Toward Green Hotels (pp. 21–29). Springer, Singapore. https://doi.org/10.1007/978-981-10-1718-6_3 Krisyanti, K., Situmeang, I. V., & Priliantini, A. (2020). Pengaruh Kampanye #PantangPlastik terhadap Sikap Ramah Lingkungan (Survei pada Pengikut Instagram @GreenpeaceID). Jurnal Komunika : Jurnal Komunikasi, Media dan Informatika, 9(1), 40–51. https://doi.org/10.31504/komunika.v9i1.2387 Kusuma, V. A. (2021). Pengaruh Terpaan Konten Instagram @Folkative Terhadap Minat Literasi Bagi Followers. Universitas Islam Negeri Sunan Ampel. Matondang, A. R. N., Putri, A. Z., Solin, A. E. B., Pohan, B. M., Harahap, N., Rosmalina, R., Putri, R. D., & Handayani, S. (2023). Persepsi Mahasiswa UINSU Terhadap Konten Pandawara Grup Dalam Meningkatkan Kesadaran Peduli Lingkungan. INNOVATIVE: Journal Of Social Science Research, 3(6), 3372–3383. Meisner, M. (2015). Environmental Communication: What it is and Why it Matters. https://meisner.ca/2015/11/30/environmental-communication-what-it-is-and-why-it-matters/#:~:text=%22Communication Munasaroh, S. A. (2021). Budaya Komunikasi pada Pengguna Media Sosial Facebook di Era New Media. Al-Ittishol: Jurnal Komunikasi dan Penyiaran Islam, 2(2), 82–96. https://doi.org/10.51339/ittishol.v2i2.309 Prasetyo, K. Amrullah, H. F., & Endri, E.P. (2021). Utilization of Social Media Instagram @satgascovid19.id in Fulfilling The Need For Information About Covid-19. e-Bangi Journal of Social Science and Humanities, 18(7), 309-318. Rafiq, A. (2020). Dampak Media Sosial terhadap Perubahan Sosial Suatu Masyarakat. Global Komunika, 1(1), 18–29. Ratnamulyani, I. A., & Maksudi, B. I. (2018). Peran Media Sosial dalam Peningkatan Partisipasi Pemilih Pemula Dikalangan Pelajar di Kabupaten Bogor. Sosiohumaniora - Jurnal Ilmu-Ilmu Sosial dan Humaniora, 20(2), 154–161. https://doi.org/10.24198/sosiohumaniora.v20i2.13965 Rubiyanti, N., San, L. Y., Widodo, A., Zhee, L. Y., Silvianita, A., & Hock, N. T. (2023). Bibliometric analysis of honeycomb model: research trend in social media marketing. 12936, 129361O. https://doi.org/10.1117/12.3011830 Salam, O. D. (2020). Personal Branding Digital Natives di Era Komunikasi Media Baru (Analisis Personal Branding di Media Sosial Instagram). JURNAL BECOSS, 2(1), 19–30. https://doi.org/10.21512/becossjournal.v2i1.6070 Sumardi, R. S., Mahomed, A. S. B., & Aziz, Y. A. (2025). Bibliometric Analysis of Stimulus-Organism-Response Theory: Past Developments, Current Applications, and Future Trends. International Journal of Academic Research in Business & Social Sciences, 15(1). https://doi.org/10.6007/ijarbss/v15-i1/23784 Sumargo, B. (2020). Teknik Sampling. Jakarta: UNJ Press. Tran, M. T. (2024). The Role of Social Media in Communicating Environmental Information From AI-Driven Geospatial Technologies. Advances in Geospatial Technologies Book Series, 327–344. https://doi.org/10.4018/979-8-3693-8104-5.ch014 Watie, E. D. S. (2011). Komunikasi dan Media Sosial (Communications and Social Media). The Messenger, 3(2), 69–75. Zamroni, M. (2022). Filsafat Komunikasi (A. Farisi, Ed.). Yogyakarta: IRCiSoD.